From cash- to securities-driven euro area repo markets: The role of financial stress and safe asset scarcity - Claus Brand; Lorenzo Ferrante; Antoine Hubert (European Central Bank (ECB), 2019)
Focussing on repo specialness premia, using ISIN-specific transaction-by-transaction data of one-day maturity repos, we document a gradual shift from cash- to securities-driven transactions in euro area repo markets over the period 2010-2018. Compared to earlier studies focussing only on specific sub-periods or market segments we extend, illustrate, and validate evidence on financial frictions that are relevant in driving repo premia: controlling for a comprehensive range of bond-market specific characteristics, we show that repo premia have been systematically affected by fragmentation in the sovereign space, bank funding stress, and safe asset scarcity. These channels exhibit very strong country-specific differences, as also reflected by large discrepancies in country-specific interest rates on General Collateral. To ensure robustness of our empirical findings, we apply panel econometric and data mining approaches in a complementary and mutually informative way.
Keywords: E52; E44; C33; C38; 330; Monetary policy; repo market; bond specialness; big data; machine learning